Effect of oxygen plasma treatment on the performance of recessed AlGaN/GaN Schottky barrier diodes. (6th January 2022) - Mao, Wei; Xu, Shihao; Wang, Haiyong; Yang, Cui; Zhao, Shenglei; Chen, Jiabo; Zhang, Yachao; Zhang, Chunfu; Zhang, Jincheng; Hao, Yue
Abstract: The treatment effect of the oxygen plasma on the performance of recessed AlGaN/GaN Schottky barrier diodes has been investigated. After the oxygen plasma treatment, the turn-on voltage and reverse leakage current are slightly changed, while the current collapse could be effectively mitigated. The X-ray photoelectron spectroscopy results suggest that a thin surface oxide layer is formed by the oxygen plasma treatment, which is responsible for the reduced current collapse. In addition, the device treated by oxygen plasma has a relatively more inhomogeneous barrier height.